Teacher Work Commitment: Analysis of Work Team Factors, Work Motivation, and Job Satisfaction - Mhd. Darwis Siagian; Rusydi Ananda; Muhammad Rifai (Newinera Publisher, 2026)
This study aims to analyze the effects of work teams and work motivation on teachers’ work commitment, with job satisfaction acting as a mediating variable, at State Islamic Senior High Schools (Madrasah Aliyah Negeri) in Langkat Regency, Indonesia. Employing a quantitative ex post facto design, data were collected from 191 teachers selected through proportional random sampling. The research instruments consisted of validated and reliable Likert-scale questionnaires, and the data were analyzed using path analysis with SPSS. The findings reveal that work teams and work motivation have significant positive effects on job satisfaction and work commitment. Job satisfaction emerges as the most dominant predictor of work commitment and significantly mediates the relationship between work teams, work motivation, and work commitment. Collectively, work teams, work motivation, and job satisfaction explain 78% of the variance in teachers’ work commitment. These results support the Integrated Model of Organizational Behavior, emphasizing the importance of both individual and organizational factors in fostering teacher commitment. The study highlights the need for strengthening collaborative work cultures, enhancing motivation, and improving job satisfaction to sustain teachers’ commitment and improve the quality of education in Islamic secondary schools.